Toxic epidermal necrolysis following treatment of pseudotumour cerebri: a case report - El Ghonemi, Mohamed (BioMed Central, 2009)
Toxic Epidermal Necrolysis and Steven-Johnson syndrome are entities on a spectrum of cutaneous reactions that usually occur as an idiosyncratic reaction to certain drugs. The distinction between TEN and SJS is based on the percentage of skin involved with SJS being less than 10% and TEN being more than 30%. They exhibit severe skin blistering and sloughing with mucosal involvement and can be fatal in many cases. Discontinuation of the offending agent is mandatory together with reduction of skin manipulation and avoiding infection. Plasmapharesis, intravenous immunoglobulins and immunosuppressants have been used with conflicting results. In this manuscript we are describing a 22 year old female patient from Egypt who presented with severe skin sloughing with mucosal involvement following carbamazepine therapy. The incriminated drug was discontinued and urgent life saving therapy in the form of broad spectrum antibiotic, immunosuppression with cyclophosphamide, Intensive Care Unit admission and nursing care was started followed by dramatic response. The clinical presentation, pathogenesis and modalities of treatment will be described in details.